Star trek, lower decks : warp your own way - North, Ryan, 1980- (IDW Publishing, a division of Idea and Design Works, LLC, 2024)
"Mariner just wants to have a normal day, but no matter what side of the bed she wakes up on, the world is ending. Literally. If she has coffee, Borg attack! If she has raktajino, cue the Romulan boarding party! And in each scenario, Mariner and her friends end up dead, sometimes the ship is destroyed--and the day starts all over again. But by exploring the different paths, you, the reader, can discover things that Mariner can't. There are inconsistencies that don't make sense--putting aside the fact that Mariner's choice of drink each morning shouldn't affect which alien races attack the ship, other facts of her world seem to change too. Something is definitely off. It's up to you to discover!"--